Proceedings of the 2018 Conference on Human Information Interaction&Retrieval - CHIIR '18 2018
DOI: 10.1145/3176349.3176387
|View full text |Cite
|
Sign up to set email alerts
|

Informing the Design of Spoken Conversational Search

Abstract: We conducted a laboratory-based observational study where pairs of people performed search tasks communicating verbally. Examination of the discourse allowed commonly used interactions to be identi ed for Spoken Conversational Search (SCS). We compared the interactions to existing models of search behaviour. We nd that SCS is more complex and interactive than traditional search. is work enhances our understanding of di erent search behaviours and proposes research opportunities for an audio-only search system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 35 publications
2
77
0
Order By: Relevance
“…For the strategy of "direct replacement" where the participants wanted to replace one name entity with another name entity, it would not be a problem if the system is a real human being (the wizard), as in the settings of this study and in the study by Trippas et al (2018). Among the three main strategies, "specific operation" and "partial repeat" could clearly tell the system how to modify the existing query.…”
Section: Patterns Of Partial Query Modificationmentioning
confidence: 96%
See 2 more Smart Citations
“…For the strategy of "direct replacement" where the participants wanted to replace one name entity with another name entity, it would not be a problem if the system is a real human being (the wizard), as in the settings of this study and in the study by Trippas et al (2018). Among the three main strategies, "specific operation" and "partial repeat" could clearly tell the system how to modify the existing query.…”
Section: Patterns Of Partial Query Modificationmentioning
confidence: 96%
“…In that case, in the next turn the participant had to speak the complete query. For the strategy of "direct replacement" where the participants wanted to replace one name entity with another name entity, it would not be a problem if the system is a real human being (the wizard), as in the settings of this study and in the study by Trippas et al (2018). It may be challenging to a computer system when the two name entities are weakly linked.…”
Section: Patterns Of Partial Query Modificationmentioning
confidence: 97%
See 1 more Smart Citation
“…Trippas et al [53] suggested that existing information seeking models do not suffice for the increased interactivity, complexity, or the agency of SCS systems.…”
Section: Introductionmentioning
confidence: 99%
“…The tasks can range from as simple as setting an alarm to more complex cases like health advice. Conversational assistants have been employed for information seeking [35] and recommendation [34] among other information systems applications. Moreover, such systems can be used as home assistants, e.g., Alexa and Google Home; or be integrated in a smartphone [1,2] or wearable devices, e.g., Apple Siri.…”
Section: Introductionmentioning
confidence: 99%